IMPLEMENTASI PENDIDIKAN SISTEM GANDA DI SEKOLAH MENENGAH KEJURUAN NEGERI KOTA BANDAR LAMPUNG - Karwan, Dedy H.; Hariri, Hasan; Rini, Riswanti (FKIP Universitas Lampung, 2016)
Implementation of Dual System Education in Public Vocational High Schools in Bandar Lampung City. This study aims to analyze the issues of dual system education in public vocational high schools (SMKN 1 and SMKN 4) Bandar Lampung focusing on the quality of dual system education management implementation through qualitative research approach. Research results show that both schools have already performed management functions including planning, implementation, and evaluation. However, the implementation phase in business and industry experienced several problems to be solved by coordination during industry work practices. Therefore, in order for quality and relevance of the public vocational high school graduates through dual system education can be achieved, the vocational high schools in Bandar Lampung need to build intensive cooperation among the stakeholders as partners in implementing dual system education. Keywords : management, dual system education, quality of graduates DOI: http://dx.doi.org/10.23960/jpp.v6.i1.201601